(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
In the article, the state of agriculture, which was the basis of the economy of the Bukhara Khanate during the Ashtarkhanids period, the relations of land ownership, the social lifestyle of the country’s citizens, their daily activities, as well as the internal struggles and political chaos of the farmers engaged in farming its impact on the social life of the population is analyzed.